Slurry for high-power medium-frequency induction furnace coil and preparation method thereof

By adjusting the usage and particle size of raw materials such as sintered plate-shaped corundum and aluminate cement, the volume change rate and porosity of the coil slurry are improved, and the problems of poor explosion-proof ability, high shrinkage rate, and poor thermal stability when used in high-power medium-frequency induction furnaces are solved, and higher explosion-proof ability, flexural strength and high temperature resistance are achieved, extending the service life of the electric furnace.

CN119638385AActive Publication Date: 2025-03-18CHUANGSHINA NEW MATERIALS (JIANGSU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411942754.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

When used in high-power medium-frequency induction furnaces, existing coil slurries have problems such as poor explosion-proof capability, high shrinkage rate, and poor thermal stability, resulting in unstable structure of the electric furnace and reduced service life.

Method used

The raw materials such as sintered plate-shaped corundum, bauxite clinker, aluminate cement, high-purity low-sodium α-Al2O3 micro powder, aluminum lactate powder, polypropylene fiber, silicone resin, composite active agent and modified dispersant are used to improve the volume change rate, porosity, explosion-proof ability, burn loss rate, flexural strength and pressure resistance of the slurry by adjusting the dosage and particle size.

Benefits of technology

It significantly reduces the volume change rate and porosity of the coil slurry, improves explosion-proof ability, flexural strength and pressure resistance, enhances thermal shock stability and high temperature resistance, and extends the service life of the electric furnace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638385A_ABST
    Figure CN119638385A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, in particular to slurry for a high-power medium-frequency induction furnace coil and a preparation method of the slurry. The invention solves the problems of poor thermal shock performance and high temperature resistance of the slurry after pouring. The synthetic raw materials of the slurry comprise sintered tabular corundum, bauxite clinker, aluminate cement, high-purity low-sodium alpha-Al2O3 micro powder, industrial grade aluminum lactate powder, polypropylene fiber, organic silicon resin, a composite active agent and a modified dispersing agent. The volume change rate and apparent porosity of the slurry are reduced by changing the dosage of the sintered tabular corundum and the aluminate cement and the dosage of the bauxite clinker and the alpha-Al2O3 micro powder; the anti-explosion capability of the slurry is improved by changing the dosage of the aluminum lactate powder, the polypropylene fiber and the organic silicon resin; the burning loss rate of the slurry is reduced by introducing the composite active agent and controlling the ball milling time; the strength of the slurry is improved by synthesizing the modified dispersant and controlling the mixing time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of refractory materials, and specifically relates to a slurry for a high-power medium-frequency induction furnace coil and a preparation method thereof. Background Art

[0002] Coil slurry is a material used on the surface of the coil of a medium-frequency coreless induction furnace. It mainly stabilizes the coil to prevent it from deforming during use and removal of the furnace lining. Generally, the insulation of coil slurry is good and can play an excellent insulating role between coil turns. Once the molten metal penetrates the furnace lining, the coil slurry can protect the coil from being melted by the molten metal. The greater the coil power, the greater the static voltage, the smaller the distance between the coil turns, and the worse the insulation performance of the coil. Generally, coils larger than 40 tons are called high-power medium-frequency induction furnace coils. The largest coil on the market is 90-100 tons.

[0003] At present, conventional coil slurry on the market is mainly composed of conventional cement combined with aluminum silicate and high-alumina refractory raw materials. This type of slurry requires a long baking time after adding water on site due to its high cement content, complex hydration products, and high proportion of bound water. If you are not careful, the material may burst due to baking too quickly; this type of slurry is prone to shrinkage under long-term high temperature, causing the material to crack, which is particularly prominent in high-power medium-frequency induction furnace coils. It cannot stabilize the coil well, easily causing instability in the furnace structure, and greatly reducing the service life of the furnace working lining.

[0004] In summary, today's coil slurry still has shortcomings such as poor explosion-proof ability, high shrinkage rate, and poor thermal stability, which leads to poor thermal shock resistance and high temperature resistance of the coil slurry after pouring, seriously affecting its application in industry.

[0005] Therefore, a slurry for a high-power medium-frequency induction furnace coil and a preparation method thereof are proposed. Summary of the invention

[0006] The purpose of the present invention is to design a slurry for high-power medium-frequency induction furnace coil and a preparation method thereof. The synthetic raw materials of the slurry for high-power medium-frequency induction furnace coil in the present invention include sintered plate-shaped corundum, bauxite clinker, aluminate cement, high-purity low-sodium α-Al 2 O 3 Micro powder, industrial grade 99wt% aluminum lactate powder, polypropylene fiber, silicone resin, composite active agent and modified dispersant. The present invention reduces the volume change rate of the coil slurry by changing the amount and particle size of sintered plate-shaped corundum and aluminate cement; by changing the amount and particle size of bauxite clinker and high-purity low-sodium α-Al 2 O 3The apparent porosity of the coil slurry is reduced and the volume density is increased by adjusting the dosage of the micropowder, the content of the components therein and the particle size; the explosion-proof ability of the coil slurry is improved by changing the dosage of industrial-grade 99wt% aluminum lactate powder, polypropylene fiber and silicone resin and the length and diameter of the polypropylene fiber; the burning rate of the coil slurry is reduced by introducing a composite active agent and controlling the ball milling time and the particle size of the micropowder; the flexural strength and compressive strength of the coil slurry are improved by synthesizing a modified dispersant and controlling the mixing time.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] In one aspect, the present invention provides a slurry for a high-power medium-frequency induction furnace coil. The synthetic raw materials of the slurry for a high-power medium-frequency induction furnace coil include the following components in parts by weight:

[0009] Sintered tabular corundum: 65-70 parts;

[0010] Bauxite clinker: 8-14 parts;

[0011] Aluminate cement: 8.9-14.9 parts;

[0012] High purity low sodium α-Al 2 O 3 Micro powder: 7-10 parts;

[0013] Industrial grade 99wt% aluminum lactate powder: 1-2 parts;

[0014] Polypropylene fiber: 0.05-0.1 parts;

[0015] Silicone resin: 9-13 parts;

[0016] Composite active agent: 2-4 parts;

[0017] Modified dispersant: 6 to 9 parts.

[0018] Preferably, the sintered tabular corundum is made of Al 2 O 3 After ball milling and calcination, Al 2 O 3 The mass percentage of SiO is 99.7% to 99.9%, and the rest is SiO 2 ; The particle size of the sintered plate-shaped corundum is 0.045 to 6 mm.

[0019] Preferably, the Al in the bauxite clinker 2 O 3 The mass percentage of SiO is 87% to 91%, and the rest is SiO 2 ; The particle size of the bauxite clinker is 0.075~3mm.

[0020] Preferably, the particle size of the aluminate cement is 8 to 10 μm.

[0021] Preferably, the high-purity low-sodium α-Al 2 O 3 Al in micro powder 2 O 3 The mass percentage of is 99.7% to 99.9%, and the rest is Na 2 O; the high-purity low-sodium α-Al 2 O 3 The particle size of the micro powder is 1.8 to 2.4 μm.

[0022] Preferably, the polypropylene fiber has a length of 5 to 6 mm and a diameter of 4 to 6 μm.

[0023] Preferably, the silicone resin is liquid methyl polysiloxane resin.

[0024] Another aspect of the present invention provides a method for preparing a slurry for a high-power medium-frequency induction furnace coil, the method comprising the following steps:

[0025] S1: 8.9-14.9 parts of aluminate cement, 7-10 parts of high-purity low-sodium α-Al 2 O 3 The micro powder, 1 to 2 parts of industrial grade 99 wt% aluminum lactate powder and 2 to 4 parts of composite active agent are mixed and continuously ground for 4 to 8 hours to make the particle size of the ground micro powder 2.4 to 3.0 μm, thereby obtaining functional additive A;

[0026] S2: 65-70 parts of sintered plate-shaped corundum, 8-14 parts of bauxite clinker, and 0.05-0.1 parts of polypropylene fiber are put into a mixer and mixed for 5-7 minutes to obtain a premix B;

[0027] S3: putting the functional additive A, the premix B and 6 to 9 parts of the modified dispersant into a mixer and mixing for 14 to 18 minutes to obtain powder C;

[0028] S4: before pouring, the powder C is mixed with 9 to 13 parts of silicone resin for 2 hours to obtain the slurry for the high-power medium-frequency induction furnace coil.

[0029] Preferably, the preparation method of the composite active agent in S1 is: ball-milling 8 to 10 parts of graphite and 3 to 5 parts of silicon powder, using water as a medium for ball-milling for 3 hours, and drying to obtain the composite active agent.

[0030] Preferably, the preparation method of the modified dispersant in S3 is: dissolving 3 to 5 parts of sodium carboxymethyl cellulose in 10 parts of deionized water to obtain mixture one; adding 2 parts of melamine to the mixture one and stirring for 30 minutes to obtain mixture two; reacting the mixture two in a closed manner at 130 to 150° C. for 8 hours, cooling to room temperature after the reaction is completed, washing and drying to obtain the modified dispersant.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The present invention reduces the volume change rate of the coil slurry by changing the dosage and particle size of sintered plate-like corundum and aluminate cement. Compared with traditional corundum powder, the sintered plate-like corundum selected in the present invention has the advantages of small open pores, low apparent porosity, low water absorption, more internal closed pores, and good thermal shock resistance and spalling resistance. Sintered plate-like corundum has excellent volume stability at high temperatures and relatively small reburning shrinkage. Aluminate cement has excellent high temperature tolerance, and its high temperature strength is usually higher than that of ordinary Portland cement. It can maintain high strength and stability at high temperatures. Therefore, the coil slurry of the present invention has good thermal shock stability and high temperature resistance when used at high temperatures; the addition of sintered plate-like corundum helps the sintering process of aluminate cement, especially at high temperatures, the CA / CA formed by the hydration reaction of aluminate cement 2 The mineral has a strong bonding ability, which can help the sintered plate-shaped corundum to better combine together during the sintering process. The final volume change rate of the coil slurry after sintering at 1050°C is -0.04%, and the volume change rate after sintering at 1500°C is -0.14%.

[0033] 2. The present invention changes the bauxite clinker and high-purity low-sodium α-Al 2 O 3 The amount of micro powder, the content of components therein and the particle size are adjusted to reduce the apparent porosity of the coil slurry and increase the volume density. 2 O 3 The micro powder easily reacts with SiO2 in the bauxite clinker at high temperature. 2 The reaction generates a large amount of rod-shaped or needle-shaped mullite. The formation of mullite can significantly reduce the porosity of the material and densify the material, thereby reducing the apparent porosity of the slurry and improving the thermal shock stability of the slurry. The apparent porosity of the final slurry after sintering at 1050°C is 10.3%, and the bulk density is 2.86g / cm 3 ; After sintering at 1500℃, the apparent porosity is 10.2% and the bulk density is 2.82g / cm 3 .

[0034] 3. The present invention improves the explosion-proof ability of the coil slurry by changing the amount of industrial-grade 99wt% aluminum lactate powder, polypropylene fiber and silicone resin, as well as the length and diameter of the polypropylene fiber. The aluminum lactate selected in the present invention can greatly improve the explosion-proof property of the coil slurry, because after the aluminum lactate and the free water in the liquid methylpolysiloxane resin are dehydrated and gelled, a network of microcracks will be generated in the matrix, thereby increasing the air permeability of the material and preventing the slurry from bursting. At the same time, a certain amount of polypropylene fiber is also introduced into the present invention, which can solve the explosion problem caused by the rapid baking of the coil slurry and improve the high temperature resistance of the slurry. Finally, the coil slurry does not burst at 1000°C.

[0035] 4. The present invention reduces the burning rate of coil slurry by introducing a composite active agent and controlling the ball milling time and the particle size of the micropowder. The introduction of the composite active agent can promote the formation and stability of minerals in the coil slurry and reduce the risk of cracking or damage of the coil slurry during high-temperature cooling; the grinding time is controlled so that the α-Al 2 O 3 The micro powder has higher activity and filling property, which can reduce the amount of liquid methyl polysiloxane resin added and fill the gaps of the pores. These pores are filled with α-Al 2 O 3 After the micro powder is filled, only a very small amount of pores remain with free water in the methyl polysiloxane resin, which reduces the loss of the coil slurry during the rapid baking process, thereby improving the thermal shock stability and high temperature resistance of the slurry. The final burnout rate of the coil slurry after burning at 1050℃ for 2 hours is 0.32%, and the burnout rate after burning at 1500℃ for 2 hours is 1.08%.

[0036] 5. The present invention improves the flexural strength and compressive strength of the coil slurry by synthesizing a modified dispersant and controlling the mixing time. The main function of the modified dispersant is to improve the dispersibility of the particles in the coil slurry, so that the particles are evenly distributed, reduce the agglomeration phenomenon caused by the mutual attraction between the particles, and improve the microstructure between the components, so that the mixture can be more uniform and have better fluidity, thereby improving its flexural strength and compressive strength; controlling the mixing time is conducive to the interaction between the components, and the components are evenly mixed to achieve the best effect, and finally improve the flexural strength and compressive strength of the coil slurry. The flexural strength of the coil slurry after being fired at 1500°C for 2 hours is 27.9MPa, and the compressive strength after being fired at 1500°C for 2 hours is 198.6MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a volume change rate diagram of Example 1, Example 3, Examples 6-8, Examples 10-11, Examples 13-16 and Comparative Examples 1-3 in the present invention after sintering at different temperatures. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Specific reference Figure 1 The present invention provides a slurry for a high-power medium-frequency induction furnace coil and a preparation method thereof. The technical scheme is as follows:

[0040] Example 1

[0041] Preparation of composite active agent:

[0042] 8 parts of graphite and 3 parts of silicon powder were ball-milled for 3 hours using water as a medium, and then dried to obtain the composite active agent.

[0043] Preparation of modified dispersant:

[0044] Dissolve 3 parts of sodium carboxymethyl cellulose in 10 parts of deionized water to obtain mixture one; add 2 parts of melamine to the mixture one and stir for 30 minutes to obtain mixture two; react the mixture two in a closed manner at 130° C. for 8 hours, cool to room temperature after the reaction, wash and dry to obtain the modified dispersant.

[0045] Preparation of slurry for high power medium frequency induction furnace coil:

[0046] S1 is made of 8.9 parts of aluminate cement, 7 parts of high-purity low-sodium α-Al 2 O 3 The micro powder, 1 part of industrial grade 99 wt% aluminum lactate powder and 2 parts of composite active agent were mixed and continuously ground for 4 hours to make the particle size of the ground micro powder 2.4 μm, thereby obtaining functional additive A;

[0047] S2: 65 parts of sintered plate-shaped corundum, 10 parts of bauxite clinker, and 0.1 parts of polypropylene fiber are put into a mixer and mixed for 5 minutes to obtain a premix B;

[0048] S3: putting the functional additive A, the premix B and 6 parts of the modified dispersant into a mixer and mixing for 14 minutes to obtain powder C;

[0049] S4: Mix the powder C and 9 parts of silicone resin for 2 hours before pouring to obtain the slurry for the high-power medium-frequency induction furnace coil.

[0050] Example 2-16

[0051] Referring to the parameter conditions of the preparation method in Example 1, the specific differences are shown in Table 1.

[0052] Table 1 Parameter conditions of Examples 1-16

[0053]

[0054] Comparative Example 1 refers to the parameter conditions of the preparation method in Example 1, except that no aluminate cement is added.

[0055] Comparative Example 2 refers to the parameter conditions of the preparation method in Example 1, except that silicate cement is used instead of aluminate cement.

[0056] Comparative Example 3 refers to the parameter conditions of the preparation method in Example 1, except that corundum powder is used instead of sintered plate-like corundum.

[0057] Example 17 Volume Change Rate Test

[0058] The coil slurry was cast into standard test blocks of 40×40×160 mm in size using a triple mold, and the volume change rates of Examples 1-16 and Comparative Examples 1-3 after firing at 1050°C and 1500°C were tested. "-" represents volume shrinkage after casting. The results are shown in Table 2. The volume change rates of Examples 1, 3, 6-8, 10-11, 13-16 and Comparative Examples 1-3 after firing at different temperatures are shown in Table 2. Figure 1 shown.

[0059] Table 2 Volume change rate test of Examples 1-16 and Comparative Examples 1-3

[0060] Example Volume change rate after sintering at 1050℃ / % Volume change rate after sintering at 1500℃ / % Example 1 -0.21 -0.32 Example 2 -0.17 -0.29 Example 3 -0.15 -0.26 Example 4 -0.18 -0.28 Example 5 -0.20 -0.31 Example 6 -0.23 -0.32 Example 7 -0.13 -0.23 Example 8 -0.16 -0.25 Example 9 -0.12 -0.22 Example 10 -0.09 -0.20 Embodiment 11 -0.11 -0.23 Example 12 -0.07 -0.17 Embodiment 13 -0.06 -0.15 Embodiment 14 -0.08 -0.16 Embodiment 15 -0.04 -0.14 Example 16 -0.06 -0.15 Comparative Example 1 -0.35 -0.48 Comparative Example 2 -0.28 -0.37 Comparative Example 3 -0.23 -0.35

[0061] From Table 2 and Figure 1 It can be found that in Comparative Example 1, aluminate cement was not added, and the volume change rate of the coil slurry was relatively high, indicating that the addition of aluminate cement can make the coil slurry have better high temperature resistance; in Comparative Example 2, silicate cement was used instead of aluminate cement, and the volume change rate of the coil slurry was significantly improved, because the high temperature resistance of aluminate cement is usually higher than that of ordinary silicate cement, and the high temperature resistance of the slurry can be improved by adding aluminate cement; in Comparative Example 3, corundum powder was used instead of sintered plate-like corundum, and the volume change rate of the coil slurry also increased. This is because the sintered plate-like corundum after ball milling and calcination has a lower apparent porosity than ordinary corundum powder and has stronger high temperature resistance. Figure 1In Examples 1-6, the amount of sintered plate-shaped corundum was changed. Finally, when the amount was 67 parts, the volume change rate of the coil slurry was the smallest, because the sintered plate-shaped corundum selected in the present invention has the advantages of small open pores, low apparent porosity, low water absorption, more internal closed pores, good thermal shock resistance and anti-flaking performance. The sintered plate-shaped corundum has excellent volume stability at high temperature and relatively small reburning shrinkage. In Examples 7-11, the Al in the sintered plate-shaped corundum was changed. 2 O 3 The content and particle size of Al 2 O 3 The volume change rate of Example 10 after sintering at 1050°C is -0.09%, and the volume change rate after sintering at 1500°C is -0.20%; in Examples 12-16, the amount and particle size of aluminate cement are changed. When the amount of aluminate cement is 12.9 parts and the particle size is 1.5 μm, the volume change rate of the coil slurry is the smallest. The volume change rate of Example 15 after sintering at 1050°C is -0.04%, and the volume change rate after sintering at 1500°C is -0.14%. Because aluminate cement has excellent high temperature tolerance, the main mineral phase is CA / CA 2 The main characteristic of CA is to ensure that the coil slurry has early demoulding strength. 2 The main characteristic of the invention is to ensure that the coil slurry has certain high temperature resistance and promote the high temperature sintering of the coil slurry, so as to ensure that the coil slurry has good medium and high temperature performance. Therefore, the coil slurry of the invention has good high temperature resistance and thermal shock stability when used at high temperature. However, the introduction of too much aluminate cement will form complex hydration products and a high proportion of bound water, which will lead to a prolonged baking time. The addition of sintered plate-shaped corundum helps the sintering process of aluminate cement, especially at high temperature, the CA / CA formed by the hydration reaction of aluminate cement 2 The mineral has a strong bonding ability, which can help the sintered tabular corundum to better bond together during the sintering process.

[0062] Examples 18-32

[0063] Referring to the parameters of the preparation method in Example 15, the difference is that the bauxite clinker and the high-purity low-sodium α-Al 2 O 3 The specific differences in the dosage of micro powder, its component content and particle size are shown in Table 3.

[0064] Table 3 Parameter conditions of Example 15 and Examples 18-32

[0065]

[0066]

[0067] Comparative Example 4 refers to the parameter conditions of the preparation method in Example 15, except that no bauxite clinker is added.

[0068] Comparative Example 5 refers to the parameters of the preparation method in Example 15, except that high-purity low-sodium α-Al 2 O 3 Micro powder.

[0069] Comparative Example 6 refers to the parameters of the preparation method in Example 15, except that ordinary α-Al 2 O 3 Micro powder replaces high purity low sodium α-Al 2 O 3 Micro powder.

[0070] Example 33 Apparent porosity and bulk density test

[0071] The coil slurry was cast into standard test blocks of 40×40×160 mm using a triple mold, and the apparent porosity and volume density of Example 15, Examples 18-32 and Comparative Examples 4-6 after sintering at 1050°C and 1500°C were tested. The results are shown in Table 4.

[0072] Table 4 Apparent porosity and bulk density test of Example 15, Examples 18-32 and Comparative Examples 4-6

[0073]

[0074]

[0075] It can be found from Table 4 that in Comparative Example 4, no bauxite clinker is added, and the apparent porosity of the coil slurry is significantly increased and the bulk density is significantly decreased, because the presence of bauxite clinker can improve the high temperature strength of the coil slurry and help it form a dense structure; in Comparative Example 5, no high-purity low-sodium α-Al 2 O 3 The apparent porosity of the powder and coil slurry is also higher, and the bulk density is also significantly reduced, because the high-purity low-sodium α-Al 2 O 3 The presence of micropowder can improve the thermal shock resistance of the coil slurry, reduce the porosity of the slurry, and make the material denser and stronger; in Comparative Example 6, ordinary α-Al 2 O 3 Micro powder replaces high purity low sodium α-Al 2 O 3 The apparent porosity of the powder and coil slurry is higher than that of the example, and the volume density is lowered. This is because α-Al 2 O 3The sodium in the micropowder can form a low melting point substance with other raw materials at high temperature, which reduces the high temperature resistance of the material and easily causes the material to shrink at high temperature, thereby causing the material to crack and be damaged. Therefore, the high-purity low-sodium α-Al 2 O 3 In Examples 15 and 18-20, the amount of bauxite clinker was changed, and the apparent porosity of the coil slurry first decreased and then increased, and the bulk density first increased and then decreased. When the amount of bauxite clinker was 10 parts, the apparent porosity of Example 18 after sintering at 1050°C was 11.5%, and the bulk density was 2.71 g / cm 3 The apparent porosity after sintering at 1500℃ is 11.4% and the bulk density is 2.68g / cm 3 In Examples 21-24, the Al content in the bauxite clinker was changed. 2 O 3 Example 23 shows the best performance, with an apparent porosity of 11.1% and a bulk density of 2.78 g / cm after sintering at 1050°C. 3 The apparent porosity after sintering at 1500℃ is 11.2% and the bulk density is 2.74g / cm 3 In Examples 25-27, high purity low sodium α-Al 2 O 3 When the amount of micro powder is 8 parts, the performance of Example 25 is the best. At this time, the apparent porosity after sintering at 1050°C is 10.8%, and the bulk density is 2.81 g / cm 3 The apparent porosity after sintering at 1500℃ is 10.9% and the bulk density is 2.78g / cm 3 , because the α-Al 2 O 3 The micro powder has a small particle size, so it has excellent specific surface area and sintering activity, and it is easy to react with SiO2 in bauxite clinker at high temperature. 2 The reaction generates rod-shaped or needle-shaped mullite, which not only has excellent high-temperature volume stability, but also can densify the material, reduce the porosity of the coil slurry, and improve the high-temperature resistance and thermal shock stability of the coil slurry; in Examples 28-32, the high-purity low-sodium α-Al 2 O 3 Al in micro powder 2 O 3 Example 31 shows the best performance in terms of content and particle size. After sintering at 1050°C, the apparent porosity is 10.3 and the bulk density is 2.86 g / cm 3 The apparent porosity after sintering at 1500℃ is 10.2% and the bulk density is 2.82g / cm 3 .

[0076] Examples 34-48

[0077] Referring to the parameter conditions of the preparation method in Example 31, the difference lies in that the amount of industrial grade 99wt% aluminum lactate powder, polypropylene fiber and silicone resin, as well as the length and diameter of the polypropylene fiber are changed. The specific differences are shown in Table 5.

[0078] Table 5 Parameters and conditions of Example 31 and Examples 34-48

[0079]

[0080] Comparative Example 7 refers to the parameter conditions of the preparation method in Example 31, except that no polypropylene fiber is added.

[0081] Comparative Example 8 refers to the parameter conditions of the preparation method in Example 31, except that deionized water is used instead of the silicone resin.

[0082] Example 49 Explosion-proof Performance Test

[0083] Example 31, Examples 34-48 and Comparative Examples 7-8 were made into 115×115×115mm samples using a triple mold to test the explosion-proof performance. The cast samples were demolded and placed in a re-firing furnace. The temperature was raised from room temperature to 1000°C at a heating rate of 15°C / min. During this process, the temperature at which the slurry burst was recorded as a basis for judging whether the material can be quickly baked. v represents that the slurry has passed the anti-burst test at this temperature, and x represents that the slurry bursts at this temperature. The results are shown in Table 6.

[0084] Table 6 Explosion-proof performance test of Example 31, Examples 34-48 and Comparative Examples 7-8

[0085]

[0086] As can be seen from Table 6, in Comparative Example 7, no polypropylene fiber was added, and the coil slurry exploded at 500°C, and the explosion-proof performance of the coil slurry was poor at this time; in Comparative Example 8, deionized water was used instead of silicone resin, and the coil slurry also exploded at 500°C, indicating that deionized water as a mixed liquid cannot improve the high temperature resistance of the coil slurry. In Example 31 and Examples 34-35, the amount of industrial-grade 99wt% aluminum lactate powder was changed, and the coil slurry had the best explosion-proof performance when the amount was 1.5 parts. Example 34 exploded at 700°C, because the industrial-grade 99wt% aluminum lactate powder is a new type of alkaline emulsion explosion-proof agent, composed of a multi-nuclear complex polymerized with hydroxylated aluminum ions, can be effectively dissolved in water, and does not produce toxic gases due to heating. After heating, it becomes Al 2 O 3, so it has strong high temperature resistance. The introduction of aluminum lactate can improve the explosion-proof performance of the fast-baked coil slurry, because aluminum lactate can react with the free water in the liquid methyl polysiloxane resin to dehydrate and gel, produce mesh microcracks in the matrix, thereby increasing the air permeability of the material and preventing the slurry from bursting. In Examples 36-40, the amount of polypropylene fiber is changed, and the explosion-proof performance of Example 37 is better, and bursting occurs at 700°C, because the fibers of the coil slurry shrink, melt or carbonize rapidly after being heated, forming elongated pores in the slurry, which is conducive to the rapid discharge of water vapor generated by heating in the coil slurry, rather than accumulating in the coil slurry to form a large steam pressure, thereby improving the explosion-proof performance of the coil slurry. In Examples 41-44, the length and diameter of the polypropylene fiber are changed, and Example 43 has the best explosion-proof performance, and bursting occurs at 700-1000°C. In Examples 45-48, the dosage of the silicone resin was changed, and the explosion-proof performance was best when the dosage was 11 parts. Example 46 still did not explode at 1000°C, and had strong high temperature resistance and thermal shock stability. Because the use of resin instead of water in the coil slurry can greatly improve the performance of the coil slurry, and due to the high solid content and low free water in the resin, cracking can be avoided after pouring, and the purpose of rapid baking without explosion can be achieved. Liquid methyl polysiloxane resin is a bulk resin with a highly cross-linked structure. It has high hardness after curing, is easy to combine with inorganic substances, has high high temperature resistance, and is combined in the slurry in the form of Si-O bonds and Si-C bonds. Therefore, the coil slurry combined with the resin under high temperature conditions has strong adhesion, can tightly combine aluminum lactate powder and polypropylene fiber, and jointly improve the explosion-proof performance of the coil slurry, and also has excellent high temperature resistance.

[0087] Examples 50-60

[0088] Referring to the parameter conditions of the preparation method in Example 46, the difference lies in that the preparation parameters of the synthetic composite active agent, the ball milling time and the particle size of the micropowder are changed. The specific differences are shown in Table 7.

[0089] Table 7 Parameters and conditions of Example 46 and Examples 50-60

[0090]

[0091]

[0092] Comparative Example 9 refers to the parameter conditions of the preparation method in Example 46, except that no composite active agent is added.

[0093] Comparative Example 10 refers to the parameter conditions of the preparation method in Example 46, except that only graphite is included in the composite active agent.

[0094] Comparative Example 11 refers to the parameter conditions of the preparation method in Example 46, except that ball milling is not performed.

[0095] Example 61 Burning Rate Test

[0096] Example 46, Examples 50-60 and Comparative Examples 9-11 were cast into standard test blocks of 40×40×160 mm using a triple mold, and the burnout rates were tested after firing at 1050°C and 1500°C for 2 hours. The results are shown in Table 8.

[0097] Table 8 Burning rate test of Example 46, Examples 50-60 and Comparative Examples 9-11

[0098] Example Burning rate at 1050℃×2h / % Burning rate at 1500℃×2h / % Embodiment 46 0.65 1.40 Embodiment 50 0.58 1.33 Embodiment 51 0.63 1.38 Embodiment 52 0.51 1.27 Embodiment 53 0.54 1.32 Embodiment 54 0.46 1.22 Embodiment 55 0.50 1.26 Embodiment 56 0.40 1.17 Embodiment 57 0.45 1.22 Embodiment 58 0.36 1.13 Embodiment 59 0.32 1.08 Embodiment 60 0.35 1.11 Comparative Example 9 1.03 2.25 Comparative Example 10 0.72 1.54 Comparative Example 11 1.62 3.66

[0099] It can be found from Table 8 that in Comparative Example 9, no composite active agent was added, and the burn-up rate of the coil slurry was significantly higher than that of the embodiment, indicating that the presence of the composite active agent can reduce the burn-up rate of the coil slurry; in Comparative Example 10, the graphite in the composite active agent was removed, and the burn-up rate of the coil slurry increased, indicating that the presence of graphite can improve the overall performance of the composite active agent, thereby reducing the burn-up rate of the coil slurry; in Comparative Example 11, no ball milling was performed, and the burn-up rate of the coil slurry was very high, indicating that without ball milling, the particle size of the material was too large, which was easily damaged during the subsequent sintering process, thereby increasing the burn-up rate. In Examples 46 and 50-53, the amount of graphite and silicon powder was changed. The burnout rate of the coil slurry was the lowest when the amount of graphite was 9 parts and the amount of silicon powder was 4 parts. The burnout rate of Example 52 after burning at 1050°C for 2 hours was 0.51%, and the burnout rate after burning at 1500°C for 2 hours was 1.27%. In Examples 54-55, the amount of the composite active agent was changed. The burnout rate of Example 54 was the lowest. The burnout rate after burning at 1050°C for 2 hours was 0.46%, and the burnout rate after burning at 1500°C for 2 hours was 1. 22%, because the introduction of the composite active agent can promote the formation and stability of minerals in the coil slurry, and reduce the risk of cracking or breakage of the coil slurry during high-temperature cooling; in Examples 56-60, the ball milling time and the particle size of the micropowder are changed. The coil slurry has the lowest burnout rate when the ball milling time is 6h and the micropowder particle size is 2.8μm. At this time, the burnout rate of Example 59 after being burned at 1050℃ for 2 hours is 0.32%, and the burnout rate after being burned at 1500℃ for 2 hours is 1.08%. This is because the grinding time is controlled to make the α-Al 2 O 3 Micro powder has higher activity and is easier to fill. It also reduces the amount of liquid methyl polysiloxane resin added and has the advantage of excellent filling of pores and gaps. These pores are filled with α-Al 2 O 3After the micro powder is filled, only a very small amount of free water in the methyl polysiloxane resin remains in the pores, which reduces the loss of the coil slurry during the rapid baking process, thereby improving the thermal shock stability and high temperature resistance of the slurry.

[0100] Examples 62-72

[0101] Referring to the parameter conditions of the preparation method in Example 59, the difference is that the preparation parameters of the synthetic modified dispersant and the mixing time are changed. The specific differences are shown in Table 9.

[0102] Table 9 Parameters and conditions of Example 59 and Examples 62-72

[0103]

[0104]

[0105] Comparative Example 12 refers to the parameter conditions of the preparation method in Example 59, except that no modified dispersant is added.

[0106] Comparative Example 13 refers to the parameter conditions of the preparation method in Example 59, except that the reaction temperature in the synthesis of the modified dispersant is 200°C.

[0107] Comparative Example 14 refers to the parameter conditions of the preparation method in Example 59, except that the reaction temperature in the synthesis of the modified dispersant is 80°C.

[0108] Example 73 Flexural Strength and Compressive Strength Test

[0109] Example 59, Examples 62-72 and Comparative Examples 12-14 were respectively cast into standard test blocks of 40×40×160 mm using a triple mold, and the flexural and compressive strengths of the test blocks were tested at corresponding temperatures. The results are shown in Table 10.

[0110] Table 10 Flexural strength and compressive strength tests of Example 59, Examples 62-72 and Comparative Examples 12-14

[0111]

[0112] It can be found from Table 10 that in Comparative Example 12, without adding the modified dispersant, the flexural strength and compressive strength of the coil slurry are significantly reduced, indicating that the modified dispersant plays a certain auxiliary role in the slurry, helping the slurry to improve the high temperature resistance and thermal shock stability; in Comparative Example 13, when the temperature of the synthetic modified dispersant becomes 200°C, the flexural strength and compressive strength of the coil slurry decrease, because when the temperature is too high, the cross-linking between the polymers is too tight, which will make the coil slurry easy to crack, thereby reducing the high temperature resistance and thermal shock stability; in Comparative Example 14, when the temperature of the synthetic modified dispersant becomes 80°C, the flexural strength and compressive strength of the coil slurry will also decrease, because the temperature is too low, the cross-linking reaction is not sufficient, and the modified dispersant is difficult to achieve the expected effect, thereby reducing the high temperature resistance of the coil slurry. In Example 59 and Examples 62-65, the preparation parameters of the modified dispersant were changed. At this time, the effect of Example 64 was optimal, and the flexural strength and compressive strength reached the highest. In Examples 66-68, the amount of the modified dispersant was changed. The flexural strength and compressive strength were the highest when the amount of the modified dispersant was 8 parts. The flexural strength of Example 67 after being fired at 1500°C for 2 hours was 27.2 MPa, and the compressive strength after being fired at 1500°C for 2 hours was 197.9 MPa. The main function of the modified dispersant is to improve the dispersibility of the particles in the coil slurry, make the particles evenly distributed, reduce the agglomeration phenomenon caused by the mutual attraction between the particles, and improve the microstructure between the components, so that the mixture can be more uniform and have better fluidity, thereby improving its flexural strength and compressive strength. In Examples 69-72, the mixing time was changed. At this time, the flexural strength and compressive strength of Example 71 were the highest. The flexural strength after calcining at 1500°C for 2 hours was 27.9 MPa, and the compressive strength after calcining at 1500°C for 2 hours was 198.6 MPa. This is because controlling the mixing time is beneficial to the interaction between the components and allows the components to be evenly mixed to achieve the best effect, ultimately improving the flexural strength and compressive strength of the coil slurry.

[0113] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A slurry for high-power medium-frequency induction furnace coil, characterized in that: The synthetic raw materials of the slurry for high-power medium-frequency induction furnace coil include the following components by weight: Sintered tabular corundum: 65-70 parts; Bauxite clinker: 8-14 parts; Aluminate cement: 8.9-14.9 parts; High-purity low-sodium α-Al2O3 powder: 7-10 parts; Industrial grade 99wt% aluminum lactate powder: 1-2 parts; Polypropylene fiber: 0.05-0.1 parts; Silicone resin: 9-13 parts; Composite active agent: 2-4 parts; Modified dispersant: 6 to 9 parts.

2. The slurry for high-power medium-frequency induction furnace coil according to claim 1, characterized in that: The sintered plate-shaped corundum is obtained by calcining Al2O3 after ball milling into balls, wherein the mass percentage of Al2O3 is 99.7% to 99.9%, and the rest is SiO2; the particle size of the sintered plate-shaped corundum is 0.045 to 6 mm.

3. The slurry for high-power medium-frequency induction furnace coil according to claim 1, characterized in that: The mass percentage of Al2O3 in the bauxite clinker is 87% to 91%, and the rest is SiO2; the particle size of the bauxite clinker is 0.075 to 3 mm.

4. The slurry for high-power medium-frequency induction furnace coil according to claim 1, characterized in that: The particle size of the aluminate cement is 8 to 10 μm.

5. The slurry for high-power medium-frequency induction furnace coil according to claim 1, characterized in that: The mass percentage of Al2O3 in the high-purity low-sodium α-Al2O3 micropowder is 99.7% to 99.9%, and the rest is Na2O; the particle size of the high-purity low-sodium α-Al2O3 micropowder is 1.8 to 2.4 μm.

6. The slurry for high-power medium-frequency induction furnace coil according to claim 1, characterized in that: The polypropylene fiber has a length of 5 to 6 mm and a diameter of 4 to 6 μm.

7. The slurry for high-power medium-frequency induction furnace coil according to claim 1, characterized in that: The organic silicon resin is liquid methyl polysiloxane resin.

8. A method for preparing slurry for high-power medium-frequency induction furnace coil, characterized in that: The slurry for high-power medium-frequency induction furnace coil according to claim 1 is prepared, and the preparation method comprises the following steps: S1: 8.9-14.9 parts of aluminate cement, 7-10 parts of high-purity low-sodium α-Al2O3 powder, 1-2 parts of industrial-grade 99wt% aluminum lactate powder and 2-4 parts of composite active agent are mixed and continuously ground for 4-8 hours to make the particle size of the ground powder 2.4-3.0μm to obtain functional additive A; S2: 65-70 parts of sintered plate-shaped corundum, 8-14 parts of bauxite clinker, and 0.05-0.1 parts of polypropylene fiber are put into a mixer and mixed for 5-7 minutes to obtain a premix B; S3: putting the functional additive A, the premix B and 6 to 9 parts of the modified dispersant into a mixer and mixing for 14 to 18 minutes to obtain powder C; S4: before pouring, the powder C is mixed with 9 to 13 parts of silicone resin for 2 hours to obtain the slurry for the high-power medium-frequency induction furnace coil.

9. The method for preparing a slurry for a high-power medium-frequency induction furnace coil according to claim 8, characterized in that: The preparation method of the composite active agent in S1 is: ball-milling 8 to 10 parts of graphite and 3 to 5 parts of silicon powder, using water as a medium for ball-milling for 3 hours, and drying to obtain the composite active agent.

10. The method for preparing a slurry for a high-power medium-frequency induction furnace coil according to claim 8, characterized in that: The preparation method of the modified dispersant described in S3 is: dissolving 3 to 5 parts of sodium carboxymethyl cellulose in 10 parts of deionized water to obtain mixture one; adding 2 parts of melamine to the mixture one and stirring for 30 minutes to obtain mixture two; reacting the mixture two in a closed manner at 130 to 150° C. for 8 hours, cooling to room temperature after the reaction is completed, washing and drying to obtain the modified dispersant.

Citation Information

Patent Citations

  • Fire-resistant self-flow castable

    CN103739299A

  • Coil cement for medium-frequency induction furnace and preparation method of coil cement

    CN106278314A

  • Blast furnace main iron runner castable, processing method thereof, and method for preparing blast furnace main iron runner from castable

    CN110128119A

  • Polyurethane finish paint coating for surface of floor paint and construction method thereof

    CN111777938A

  • Refractory castable capable of being quickly baked and preparation method of refractory castable

    CN116199504A